Women's entrepreneurship - McAdam, Maura (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"Drawing on the entrepreneurial ecosystem as a frame of reference, this new edition of Female Entrepreneurship - Women's Entrepreneurship, continues to challenge contemporary assumptions regarding who or what is an entrepreneur. It draws upon relevant literature and research to enable research-led teaching delivery and provides students with a comprehensive understanding of women's entrepreneurship and a solid foundation from which they can pursue further studies. Informative but concise, Women's Entrepreneurship covers key concepts, issues, themes and approaches and provides useful suggested topics for debate. Updates include a revised chapter on Emerging Technologies and Women's Entrepreneurship, which explores digital entrepreneurship and cyberfeminism. Contextualization of Women's Entrepreneurship acknowledges the broader contextual influences on women's entrepreneurship. Finally, two new chapters have been added looking at The Entrepreneurial Ecosystem and Women's Entrepreneurship Policy. International case studies explore the socio-economic context for women's entrepreneurship in regional, national and international economies. Pedagogy to aid learning is incorporated throughout, including Learning Objectives, boxes to highlight key points, Summaries and Discussion Points, whilst signposts flag relevant podcasts, Ted Talks and online recommended reading. This book is important supplementary reading on entrepreneurship, small business management and women's and gender studies courses - it will prove particularly useful to women moving towards starting their own business as well as postgraduate students researching the topic for the first time"--
Originally entered under title: Female Entrepreneurship.
OCLC-licensed vendor bibliographic record.
Keywords: Self-employed women; Businesswomen; Women-owned business enterprises; Entrepreneurship; BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Entrepreneurship; SOCIAL SCIENCE / Women's Studies